Mobius propeller - Gretchikhin, Leonid I.; Gushtchin А. L.; Narushevitch А. А. (Vojnotehnički glasnik / Military Technical Courier, 2014)
The article gives a detailed molecular-kinetic theory of the Mobius propeller functioning and shows the implementation of its computer modelling in different exploitation conditions. The mechanisation of the Mobius propeller can be carried out in such a way that, under certain conditions, it enables using this type of propellers as a heat pump. The developed theory of the Mobius propeller functioning has been experimentally verified in laboratory conditions.